Immune infiltrate populations within distinct tumor immune microenvironments predictive of immune checkpoint treatment outcome - Brian Z Ring; Catherine T. Cronister; Huijun Z. Ring; Douglas T. Ross; Robert S. Seitz (Scientific Reports)
Abstract Understanding the dynamic tumor immune microenvironment (TIME) is important in guiding immunotherapy. We have previously validated signatures predictive of checkpoint inhibitor efficacy which distinguish immunomodulatory, mesenchymal stem-like, and mesenchymal phenotypes. Here we use twenty tumor types (7162 samples) to identify potentially conserved immune biology within these TIME spaces, genes co-expressed across distinct cell types involved these immune processes, and the association of these signatures with ICI response. One signature, which contained multiple B-cell markers, was associated with immunotherapy efficacy in three cohorts, including IMvigor210. This signature of potentially conserved B-cell biology in co-infiltrated immune cell ecosystems had a more consistent association with outcome than comparable single cell type models and likely reflects a complex immunological response involving multilayered relationships between distinct immune effector cell types. These signatures were most highly expressed in tumors with prominent immune cell invasion, however there was consistent identification of infiltrate presence in relatively immune restricted cases. This suggests that these immune population signatures may identify conserved immune cell type co-infiltrate physiology of the TIME that best captures immune physiology with potential clinical utility.